1994
DOI: 10.1007/bf01695915
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of invasive fungal infections after bone marrow transplantation in patients receiving amphotericin B inhalations during neutropenia

Abstract: The incidence of invasive fungal infections after bone marrow transplantation (BMT) was analyzed in 303 consecutive marrow graft recipients (allogeneic n = 271, autologous n = 27, syngeneic n = 5). All patients received inhalations with amphotericin B (10 mg twice daily) during neutropenia. The overall incidence of invasive fungal infections within the first 120 days after transplant was 3.6% (11/303; aspergillosis: 6; yeast infection: 5). Four of the 11 cases occurred early, and seven cases were observed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 20 publications
0
45
1
1
Order By: Relevance
“…In 40 patients undergoing allogeneic HSCT, aerosolized lipid complex (50 mg once daily for 4 days, thereafter once weekly for 13 weeks) was well tolerated and only one proven IFI was reported during the study period. 8 In a large retrospective study 9 10 mg of d-AmB was delivered twice daily during neutropenia in HSCT patients: in this cohort of patients a low cumulative incidence of IFIs was observed (3.6% at 120 days after transplant). In a more recent randomized controlled trial, 25 mg once daily of liposomal amphotericin B administered for 2 days weekly until neutrophil recovery was randomly compared with placebo in 271 patients during 407 episodes of prolonged neutropenia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In 40 patients undergoing allogeneic HSCT, aerosolized lipid complex (50 mg once daily for 4 days, thereafter once weekly for 13 weeks) was well tolerated and only one proven IFI was reported during the study period. 8 In a large retrospective study 9 10 mg of d-AmB was delivered twice daily during neutropenia in HSCT patients: in this cohort of patients a low cumulative incidence of IFIs was observed (3.6% at 120 days after transplant). In a more recent randomized controlled trial, 25 mg once daily of liposomal amphotericin B administered for 2 days weekly until neutrophil recovery was randomly compared with placebo in 271 patients during 407 episodes of prolonged neutropenia.…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies suggest that aerosolized lipidic formulations of amphotericin B could be effective in preventing airways IFIs in lung 7 and HSCT 8,9 and during prolonged neutropenia. 10 In lung transplant recipient, 50 mg of lipid complex amphotericin B was compared with 25 mg once daily of deoxycholate-amphotericin B inhalations: 7 in each arm full-dose treatment was delivered for 1 week followed by one inhalation weekly for 7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 The only large multicenter trial did not confirm these results (Level E I). 65 In a non-comparative evaluation of inhalational amphotericin B lipid complex 50 mg/d and concomitant fluconazole 400 mg/d were found to be safe in allogeneic stem cell recipients.…”
Section: Polyenesmentioning
confidence: 94%
“…28 Aerosolized amphotericin B, suggested to be useful for prophylaxis, was not confirmed as effective in a randomized evaluation. 29,30 A recent study using 2 mg/kg/day of liposomal amphotericin three times a week demonstrated little toxicity, but did not show a significant reduction in fungal infections. 31 Three large-scale series have compared Fluconazole and oral placebo, either in patients with acute leukemia or those undergoing bone marrow transplantation.…”
mentioning
confidence: 99%